Vis a Vis: Recidivism and Penal Sanction - Feoli, Marco (2019)
This article aims to provide an approximation of the possible criminogenic effects of imprisonment. The study was conducted by means of a descriptive analysis of quantitative data, which made it possible to approach the relationship that might exist between the types of penalties and criminal recidivism in Costa Rica. Several studies have sought to identify where the difference is in the exercise of the punitive power of the State in the lives of those who served a criminal sentence. In this sense, labeling theorists consider that the prison sentence generates a stigmatization process that, besides the conditions for which the prison population is selected, can multiply the possibilities of recidivism, unlike non-custodial sentence programs. This study addresses the recidivism rates of people who served a criminal sentence between January and March 2016 in Costa Rica for a two-year follow-up period. Inferences are formulated on the possibilities of social insertion of people who have completed the execution of a criminal sanction. The discussion is based on the expression "Vis a Vis" (face to face).